2015
DOI: 10.1002/2014jc010605
|View full text |Cite
|
Sign up to set email alerts
|

Advection of North Atlantic Deep Water from the Labrador Sea to the southern hemisphere

Abstract: Recently formed Labrador Seawater (LSW) and overflow water from Denmark Strait (DSOW) are main components of the Atlantic Meridional Overturning Circulation. Both exhibit a distinct chlorofluorocarbon (CFC) maximum. Here we use 25 years of CFC observations in the Atlantic to study the main features of the circulation of LSW and DSOW. From the CFC data, the age and fraction of young deep water are inferred. Due to the superior spatial data resolution compared to former attempts, regional differences in the spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(131 citation statements)
references
References 67 publications
9
115
0
Order By: Relevance
“…We find that the dLSW layer salinity is very similar from the Labrador Sea to the Flemish Cap, but is increased at the Tail of the Grand Banks, and increased further at We also show that the salinity minimum arrives at Line W before arriving at Bermuda. As Line W and Bermuda are both about 4500km downstream from the Labrador Sea, this indicates that dLSW properties travel faster along the boundary than in the interior pathway to Bermuda, which is also consistent with other studies (Bower et al, 2009;Rhein et al, 2015;Smith et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We find that the dLSW layer salinity is very similar from the Labrador Sea to the Flemish Cap, but is increased at the Tail of the Grand Banks, and increased further at We also show that the salinity minimum arrives at Line W before arriving at Bermuda. As Line W and Bermuda are both about 4500km downstream from the Labrador Sea, this indicates that dLSW properties travel faster along the boundary than in the interior pathway to Bermuda, which is also consistent with other studies (Bower et al, 2009;Rhein et al, 2015;Smith et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Rhein et al (2015) compiled 25 years of CFC data to make maps of age and fraction of young deep water. Their results imply a CFC transit time of 11 years for LSW to Line W along the boundary, which is, again, longer than our estimate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporal changes are expected to be more variable for complex food webs with mixed prey items and biota that forage from deeper seawater such as North Atlantic pilot whales (Globicephala melas) that mainly consume squid between 400 and 700 m depth [Hoydal and Lastein, 1993;Li et al, 2015]. Rahmstorf et al, 2015;Rhein et al, 2015;Yashayaev, 2007]. Rahmstorf et al, 2015;Rhein et al, 2015;Yashayaev, 2007].…”
Section: Temporal Changes In Pfos Concentrations and Mass Budgets Formentioning
confidence: 99%
“…Oceanographic studies have shown that the southward transport of northern-sourced waters in the equatorial Atlantic mainly 20 takes place between ~1300 and 4000 m depth in a ~ 100 km wide Deep Western Boundary Current (DWBC) (Lux et al, 2001;Rhein et al, 2015). Using hydrographic, geochemical, and direct velocity measurements acquired in 1993 to inverse an ocean circulation model, (Lux et al, 2001) estimated that the volumetric flow of upper North Atlantic Deep Water (NADW) occupying water depths between ~1300 and 2300 m at 4.5° S within the DWBC is 11.2 Sv (1 Sv = 10 6 m 3 s -1 ).…”
Section: Reconstructed Ocean Circulation Changes Over the Last 45 Kymentioning
confidence: 99%